“We’re All in the Same Boat” – The Experience of People With Mental Health Conditions and Non-clinical Community Members in Integrated Arts-Based Groups - Nitzan, Aya; Orkibi, Hod (Frontiers in Psychology, 2021)
In recent decades there has been a significant increase in community rehabilitation programs for people with mental health conditions. One such nationwide programs is Amitim in Israel whose mission is to foster the psychosocial rehabilitation of people with mental health conditions in the community. Amitim’s flagship program consists of arts-based groups that integrate participants with mental health conditions and non-clinical community members. To better understand the experiences of participants in these arts-based groups, five focus groups were conducted with participants from 15 integrated arts-based groups. In total, 17 people with mental health conditions and 21 non-clinical community members were interviewed for this qualitative study. Three main themes emerged from the thematic analysis: creation and expression through the arts promote well-being, self-disclosure in a safe space encourages a sense of belonging, and “we are all in the same boat.” The participants underscored the role of creation and expression through the arts in facilitating emotional expression, self-discovery, interpersonal communication, and spiritual elevation. The findings suggest that the facilitators should instill a sense of equality by enabling intergroup acquaintances without labeling participants’ mental health status. Integrated arts-based groups should be accompanied by a mental health professional who can contain and work through complex emotional situations when needed. Arts therapists who specialize in both arts and mental health are particularly suitable for this role. Overall, the interviewees reported that participation in the integrated arts-based groups positively impacted their personal recovery processes by providing a corrective experience of equality as well as enhancing a sense of belonging to the community and social relationships. The participants also reported being empowered by the final artistic event that not only enhanced their sense of visibility, competence, and aspirations for future development in personal, interpersonal, and artistic realms, but also helped to combat both self- and public stigma.